Great expectations - Dickens, Charles (Nxb. Đồng Nai, 2009)
A terrifying encounter with an escaped convict in a graveyard on the wild Kent marshes; a summons to meet the bitter, decaying Miss Havisham and her beautiful, cold-hearted ward Estella; the sudden generosity of a mysterious benefactor - these form a series of events that change the orphaned Pip's life forever, and he eagerly abandons his humble origins to begin a new life as a gentleman. Dickens' haunting late novel depicts Pip's education and development through adversity as he discovers thetrue nature of his 'great expectations'.